Evaluation of the commercial potential of intellectual-innovative technologies based on the technological audit - Kosenko, Alexandra (Academic Society of Michal Baludansky, 2015)
In the article improved the essence of the concept "technology audit", which is considered as a system of information-analytical, methodological and instrumental evaluation of commercial potential of technologies that can play a dynamic assessment of the economic situation of the developer and the potential user of technology with greater confidence than when using the existing developments. The concept of technological linkage as a tool for assessing commercial potential of technologies, which is based on a model of patent valuation Hall and Jaffeweighted citation (citation-weighted patents), which allows to establish a link between technological efficiency and effectiveness of operational and financial performance of the engineering enterprise. It defines the specific characteristics of the features of the intelligent technologies from the point of view of their market support, among which are selected those that are positive and such that carry a negative connotation. The premise of the effect of the technological lever of the developer of a technological product that uses the exclusively developed technology is technological flexibility, that is, the presence of production capacity of different modifications of a technological product on the same production lines and process equipment. The premise of the effect of technological lever at the licensee (the consumer) intelligent technology is the creation on the basis of the licensed technology food technology platform, formulation and implementation of a number of products and their modifications, as the basis of creation, which are based on the capabilities of the technology.

В статті удосконалено сутність поняття "технологічний аудит", яке розглядається як система інформаційно-аналітичної, методичної і інструментальної оцінки комерційного потенціалу технологій, що дозволяє відтворювати динамічну оцінку стану економічної ситуації розробника та потенційного споживача технологій з більшим ступенем достовірності ніж при використанні існуючих розробок. Запропоновано концепцію технологічного важеля як інструменту оцінки комерційного потенціалу технологій, в основу якої покладено модель оцінки патентів Hall і Jaffe, зважених з урахуванням цитування (citation weighted patents), що дозволяє встановити зв'язок між технологічною ефективністю та ефективністю операційної та фінансової діяльності машинобудівного підприємства. Визначено специфічні характеристики особливостей інтелектуальних технологій з точки зору їх ринкового супроводу, серед яких виділено такі, які мають позитивний характер, і такі, що несуть в собі негативний підтекст. Передумовою виникнення ефекту технологічного важеля у розробника технологічного продукту, який монопольно використовує розроблену ним технологію, є технологічна гнучкість, тобто наявність можливостей виробництва різних модифікацій технологічного продукту на одних і тих же технологічних лініях і технологічному обладнанні. Передумовою виникнення ефекту технологічного важеля у ліцензіата (споживача) інтелектуальних технологій є створення на основі ліцензованої технології продуктово- технологічної платформи, тобто розробки і реалізації низки товарів і їх модифікацій, в основу створення яких покладено можливості даної технології.
Оцінка комерційного потенціалу інтелектуально-інноваційних технологій на засадах технологічного аудиту
Keywords: technology; intellectual technology; innovation technology; commercial potential; technological audit; технології інтелектуальні; технології інноваційні; потенціал комерційний; аудит технологічний